2023
DOI: 10.1021/acs.analchem.3c02640
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Ethylamines as Electrospray-Compatible Neutral pH Buffers for Native Mass Spectrometry

Bradley T. V. Davis,
Algirdas Velyvis,
Siavash Vahidi

Abstract: Native electrospray ionization mass spectrometry (ESI-MS) has emerged as a potent tool for examining the native-like structures of macromolecular complexes. Despite its utility, the predominant "buffer" used, ammonium acetate (AmAc) with pK a values of 4.75 for acetic acid and 9.25 for ammonium, provides very little buffering capacity within the physiological pH range of 7.0−7.4. ESI-induced redox reactions alter the pH of the liquid within the ESI capillary. This can result in protein unfolding or weakening o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…With the simplicity of sample preparation, low sample consumption, high sensitivity, and high throughput, native ESI-MS has received a lot of attention in drug screening. 1,2,24,25 To optimize the native ESI-MS to explore PMIs, a variety of studies have been reported, including the type of ion source, 21,26,27 the size of ESI tips, [28][29][30][31] the buffer maintaining the native conditions, [32][33][34] and solvent additives. 22,35,36 However, only a few studies have dealt with the issue of non-specific binding between the target protein and the small molecules tested.…”
Section: Introductionmentioning
confidence: 99%
“…With the simplicity of sample preparation, low sample consumption, high sensitivity, and high throughput, native ESI-MS has received a lot of attention in drug screening. 1,2,24,25 To optimize the native ESI-MS to explore PMIs, a variety of studies have been reported, including the type of ion source, 21,26,27 the size of ESI tips, [28][29][30][31] the buffer maintaining the native conditions, [32][33][34] and solvent additives. 22,35,36 However, only a few studies have dealt with the issue of non-specific binding between the target protein and the small molecules tested.…”
Section: Introductionmentioning
confidence: 99%
“…The final steps of the ESI process, i.e., the release of gaseous analyte ions from highly charged nanodroplets, is a topic of great interest and considerable controversy. Three mechanisms have emerged as likely ion formation pathways . In the charged residue mechanism (CRM), analyte ions are released upon droplet evaporation to dryness. , The ion evaporation mechanism (IEM) proceeds with analyte ejection from the droplet, driven by Coulombic repulsion between the analyte charge and other charges on the droplet. , The chain ejection mechanism (CEM) applies to disordered polymeric analytes (such as unfolded proteins), which gradually extrude from the droplet and end up as highly charged and electrostatically stretched gaseous ions. ,, In addition to these mechanisms, various hybrid scenarios may exist. , …”
Section: Introductionmentioning
confidence: 99%